2007
DOI: 10.1111/j.1600-0501.2007.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of Schneiderian membrane perforations during sinus‐lift procedures

Abstract: This clinical study was undertaken to evaluate the prevalence of surgical complications of the sinus graft procedure and to set a protocol to repair sinus membrane perforations intraoperatively using a variety of techniques and materials. From January 2000 to May 2005, 338 patients were studied, on whom 474 sinus floor augmentation procedures were performed, and a total of 1166 dental implants were simultaneously placed. A total of 104 perforations of the sinus membrane were observed (19 were bilateral). In gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
249
2
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(291 citation statements)
references
References 10 publications
13
249
2
6
Order By: Relevance
“…To guarantee safe placement, researchers should verify in an in vivo clinical study that there is no development of sinusitis in cases of miniscrew perforation of the sinus. A case report using miniscrews (15) supported the findings of studies on maxillary sinus augmentation (sinus-lift procedure) (16)(17)(18). It found that while small, uncomplicated perforations may heal spontaneously, larger perforations in unfavorable areas can cause inflammation and other complications.…”
Section: Introductionsupporting
confidence: 55%
“…To guarantee safe placement, researchers should verify in an in vivo clinical study that there is no development of sinusitis in cases of miniscrew perforation of the sinus. A case report using miniscrews (15) supported the findings of studies on maxillary sinus augmentation (sinus-lift procedure) (16)(17)(18). It found that while small, uncomplicated perforations may heal spontaneously, larger perforations in unfavorable areas can cause inflammation and other complications.…”
Section: Introductionsupporting
confidence: 55%
“…They concluded that the sinus membrane perforation was not shown to be a significant factor in the rate of implant complications. Numerous case reports of accidental sinus perforation during implant placement conclude that the perforation did not lead to any serious sequela or morbidity [8] [9].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Estas membranas no reabsorbibles también pueden utilizarse en perforaciones en la membrana Schneideriana del seno maxilar. 18 El efecto barrera es más difícil de conseguir con las membranas reabsorbibles, por lo que al utilizar estas membranas se recomienda colocar material de injerto bajo ellas. 19 La literatura no muestra diferencias estadísticamente significativas entre el empleo de membranas reabsorbibles y no reabsorbibles en general, 20,21 aunque está publicado un mayor volumen de regeneración ósea con membranas no reabsorbibles alrededor de implantes colocados post-exodoncia.…”
Section: Guided Bone Regeneration (Gbr)unclassified